Hubungan Intensitas Penggunaan Smartphone dengan Hasil Nilai Pengetahuan Bahasa Arab Peserta Didik SDIT Quranic Al-Abror: Hubungan Intensitas Penggunaan Smartphone dengan Hasil Nilai Pengetahuan Bahasa Arab Peserta Didik SDIT Quranic Al-Abror - Yuda Prastiya; Langgeng Sutopo; Khairil Anwar (Program Studi Pendidikan Bahasa Arab, 2023)
This research is motivated by the suspicion that suboptimal knowledge scores (KI-3) are influenced in part by high smartphone usage intensity. The objectives of this research are: (1) To determine the extent of smartphone usage intensity among students at SD IT Quranic Al Abror. (2) To describe the significance of the relationship between smartphone usage intensity and Arabic language knowledge scores among students at SD IT Quranic Al Abror for the academic year 2022/2023. This is a quantitative research study using a correlation method with data analysis techniques employing Pearson Product Moment Correlation analysis. The research sample consists of 30 students. Data collection for the smartphone usage intensity variable is done through a questionnaire, while data for Arabic language knowledge scores are obtained from documents of mid-semester exams in the even semester of the academic year 2022/2023. Research instrument validation and reliability testing were conducted. The research results indicate that (1) the average smartphone usage intensity by students at SD IT Quranic Al Abror Natar Lampung Selatan is 20.5 points, which falls within the low to moderate range, (2) the significance value (r-value) is 0.002, which is less than (<) 0.05, and the Pearson Correlation value is -0.549. In conclusion, there is a significant negative relationship between smartphone usage intensity and Arabic language knowledge scores among students at SD IT Quranic Al Abror Natar Lampung Selatan.